Implementasi Scrum Pada Perancangan System Mobile Taking Order Coffee Aplikasi Berbasis Mobile - Rika Kurniawati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
System mobile taking order coffee is a mobile-based application that aims to be a bridge in the coffee distribution process from coffee farmers to distributors, coffee farmers to consumers, and also distributors to consumers. Through this system, coffee farmers, distributors, and consumers can make coffee transactions via smartphones. The design of this system uses the concept of an approach with the Scrum method. Scrum is a framework with various processes and techniques in it that focuses on breaking down major goals into smaller goals to make them easier to achieve. The use of the scrum method approach is considered capable of designing quality software that suits existing needs. In addition, it can facilitate the adoption of any changes. Scrum also has several systematic and iterative stages, so that if the product int the first sprint does not meet the required needs, then the next sprint can be developed according to the evaluation results from the previous system users. The design of this system is to facilitate coffee farmers in the process of distributing coffee with a wider market reach.